Digital Learning Media To Enhance Students’ Leaning Activities And Outcomes In Thematic Integrative Learning - Wakhibah Dwi Khusnah; Rima Asmaul Chusna (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2026)
In the 5.0 era, educators should be able to use technology to be more active and innovative. To accomplish this, educators can develop digital-based learning media. The purpose of this study is decribing digital learning media application to enhance students’ learning activities and outcomes in thematic integrative learning. The results of study is application of digital learning is very influential in active learning activities and learning outcomes. It is proven from the results of the percentage of student activity before using digital learning media which is 80% and after using digital learning media it becomes 95.7%. The learning outcomes of students showed an increase from an average score of 74 to 83 with details of students who reached passing grade 13 students to 19 students.